Meta-analysis of project-based learning in early childhood: entrepreneurial context - Anggarda Paramita Muji; Alwen Bentri; Jamaris . (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2022)
The period of early childhood is the formation and cultivation of values through habituation in children's learning activities in educational institutions, one of which is in kindergarten. This study aims to analyze project-based early childhood learning and instill entrepreneurial values in children. Systematic literature review and meta-analysis (PRISMA) was used as the method for conducting this research. The articles reviewed are 30 of the latest articles from 2019 to 2022. All articles are classified by author, year of publication, type of journal or conference, method, project learning model, and findings. The results of the study are presented as follows. (1) The search results prove that there has been an increase in the number of published articles from 2019-2021 (2) The research results show that project-based entrepreneurship learning models are being introduced to early childhood learning. (3) The project-based entrepreneurship learning model developed for kindergarten education can stimulate aspects of child development.